2021
DOI: 10.1039/d1qo00168j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidative synthesis of 1,3,4-thiadiazoles from isothiocyanates and hydrazones

Abstract: A 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ)-catalysed electrochemical synthesis of 2-amino-1,3,4-thiadiazoles from isothiocyanates and hydrazones is presented. This protocol is mild, practical, metal-free and exogenous oxidant-free, and features a broad substrate scope. Extensive mechanistic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Ma et al 126 developed a metal and oxidant-free synthesis of 1,3,4-thiadiazoles using the electrochemical oxidative method. The pre-screening of the reaction conditions was performed with isothiocyanatobenzene ( 146a ) and benzylidene hydrazine ( 148a ) using DDQ as catalyst.…”
Section: Transition Metal-free Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ma et al 126 developed a metal and oxidant-free synthesis of 1,3,4-thiadiazoles using the electrochemical oxidative method. The pre-screening of the reaction conditions was performed with isothiocyanatobenzene ( 146a ) and benzylidene hydrazine ( 148a ) using DDQ as catalyst.…”
Section: Transition Metal-free Reactionsmentioning
confidence: 99%
“…Claraz et al 120 reported the electrochemically catalysed multicomponent synthesis of CF 3 -substituted imidazolines and oxazolidines via trifluoromethylation of allylamine/[3+2] cycloaddition. The reaction conditions were optimised using N-tosyl allylamine (126) and acetonitrile (127a) as model substrates and Langlois reagent (87) as trifluoro-methylating agent. The reaction was performed in an undivided cell furnished with nickel as a cathode and carbon as anode.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Review / Short Review [71][72][73][74] The electrochemical sulfonylation/cyclization reactions between 2-alkynylthioanisoles 131 and sodium sulfinates 132 using nBu4NBF4 or nBu4NBr as electrolyte delivered sulfonated benzothiophenes 133 in 43-87% or up to 86% yields. 71,72 Thiazoles 136 and dihydrothiazoles 138 can be synthesized in 31-96% yields and up to 93% yields respectively from the electrochemical reactions of thiourea 135 with enamines 134 or enaminones 137 in the presence of HCl (aq) or trifluoromethanesulfonic acid (TfOH) in MeOH or R 4 OH.…”
Section: Synthesismentioning
confidence: 99%
“…73 Under the catalysis of 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ), the electrochemical reactions of isothiocyanates 139 and hydrazones 140 afforded 40-84% yields of 2-amino-1,3,4thiadiazoles. 74 Scheme 25 Electrochemical cascade cyclization for the synthesis of sulfonated benzothiophenes, thiazoles, dihydrothiazoles and 1,3,4thiadiazoles.…”
Section: Synthesismentioning
confidence: 99%